The alpha-tubulin gene family expressed during cell differentiation in Naegleria gruberi (The Rockefeller University Press, 1988)
Genes that direct the programmed synthesis of flagellar alpha-tubulin during the differentiation of Naegleria gruberi from amebae to flagellates have been cloned, and found to be novel with respect to gene organization, sequence, and conservation. The flagellar alpha- tubulin gene family is represented in the genome by about eight homologous DNA segments that are exceptionally similar and yet are neither identical nor arrayed in a short tandem repeat. The coding regions of three of these genes have been sequenced, two from cDNA clones and one from an intronless genomic gene. These three genes encode an identical alpha-tubulin that is conserved relative to the alpha-tubulins of other organisms except at the carboxyl terminus, where the protein is elongated by two residues and ends in a terminal glutamine instead of the canonical tyrosine. In spite of the protein conservation, the Naegleria DNA sequence has diverged markedly from the alpha-tubulin genes of other organisms, a counterexample to the idea that tubulin genes are conserved. alpha-Tubulin mRNA homologous to this gene family has not been detected in amebae. This mRNA increases markedly in abundance during the first hour of differentiation, and then decreases even more rapidly with a half-life of approximately 8 min. The abundance of physical alpha-tubulin mRNA rises and subsequently falls in parallel with the abundance of translatable flagellar tubulin mRNA and with the in vivo rate of flagellar tubulin synthesis, which indicates that flagellar tubulin synthesis is directly regulated by the relative rates of transcription and mRNA degradation.